Metastatic gastrointestinal stromal tumours-a rarest of rare presentation: a case report - Govindarajulu, Chandramouli; Gayathre, Shanmugam Papu; Ross, Kannan; Mugunthan, Kudiyarasu (International Surgery Journal, 2021)
Gastrointestinal stromal tumours (GISTs) is the most common mesenchymal tumour of the gastrointestinal tract (GIT). GISTs can occur anywhere along the GIT, more so commonly in the stomach and small intestine. They can manifest as an emergency such as obstruction, perforation of a hollow viscous or as a haemorrhage. The metastatic stage was usually detected after the histopathologic report. We report on a 29-year female para 1 live 1 (P1L1) admitted at the institute of obstetrics and gynaecology (IOG) Egmore, Chennai, as a case of right torsion ovary. The patient was taken for an emergency laparotomy. Ovaries are found to be normal and so the surgical team was called in. Per-operative diagnosis of ileo-ileal intussusception was made, followed by resection and anastomosis. Biopsy report of the specimen showed a GIST, arising from the small intestine causing the intussusception. Further follow-up of the patient with CECT abdomen showed hepatic metastasis in segments 4a and 7. GISTs tumours data on worldwide frequency is limited, especially in the 3rd world countries. Adding to the limited data GISTs present themselves in protean ways. It is then necessary to understand not only the presentation but also the complications. Multimodality approach involving early screening, dissemination of knowledge regarding various types of presentation and the tools to manage such complications, early involvement of medical gastroenterology and medical oncology along with patient education will go a long way in the management of these difficult tumours.